Remarkable Differences in Calcification between the Primary Tumor and Metastatic Lymph Nodes in a Patient with ALK-Positive Non-Small-Cell Lung Cancer - Keeya Sunata; Tetsuo Tani; Takahiko Ui; Hidehiro Irie; Yohei Funatsu; Hidefumi Koh (Case Reports in Pulmonology)
Calcified bilateral mediastinal lymph nodes are not common in malignant tumors. A 51-year-old woman presented to our hospital with a 20 mm nodule in the lower left lobe of the lung and extensive calcification in the bilateral mediastinal lymph nodes. Computed tomography indicated no calcification of the primary lesion. Immunohistochemical staining and fluorescent in situ hybridization detected an anaplastic lymphoma kinase (ALK) fusion. Treatment with alectinib, an ALK inhibitor, led to a significant reduction in tumor size and calcification in the lymph nodes. This case shows that different degrees of calcification can be associated with malignant tumors and may be reversible in some cases.